Outcome of Elastic Intramedullary Nailing of Femur Shaft Fractures in Children (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To determine the outcome of elastic intramedullary nailing of femur shaft fractures in children in terms of fracture union, final wound healing, range of movement, limb lengths and gait of the patient. Methods: We conducted a prospective study of 17 children presenting with femoral shaft fractures in Mercy Teaching Hospital from March 2014 to June 2015. The average follow up duration was 14 months (ranging from 9 to 22 months). Results: 15 (88%) out of the 17 patients had excellent outcomes in terms of fracture union, final wound healing, range of movement, limb lengths and gait. One patient went into non-union who required an additional surgery, bone grafting to achieve union. The other patient had knee stiffness not responding to physiotherapy, thus needed manipulation under anesthesia. Conclusion: It is concluded that Elastic Intramedullary Nailing of Femur Shaft Fractures in Children have excellent outcome with minimal complications. Therefore, orthopedic surgeons should adopt this procedure for the fixation of femoral diaphysial shaft fractures. Keywords: Femur shaft fractures, children, Elastic Intramedullary Nails, Outcome.